2019
DOI: 10.1002/aenm.201900611
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Generated Fireproof Gel Polymer Electrolyte with Li6.4Ga0.2La3Zr2O12 As Initiator and Ion‐Conductive Filler

Abstract: Poly(vinylidene fluoride‐co‐hexafluoropropylene) (PVDF‐HFP) based gel polymer electrolyte is regarded as a promising candidate to settle the safety issues of liquid electrolytes. However, the currently reported gel polymer electrolytes are still not safe enough owing to high amount of flammable liquid solvents contained in them. Herein, a fireproof PVDF‐HFP based gel polymer electrolyte is designed and synthesized through an in situ crosslinking method, with Li6.4Ga0.2La3Zr2O12 as initiator and ion‐conductive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
93
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(102 citation statements)
references
References 58 publications
0
93
0
Order By: Relevance
“…[ 24–26 ] Nan's group utilized the catalysis of La in dehydrofluorination and prepared poly(vinylidenefluoride) (PVDF)–Li 6.75 La 3 Zr 1.75 Ta 0.25 O 12 (LLZTO) HSE whose ionic conductivity is as high as 5 × 10 −4 S cm −1 at 25 °C. [ 26 ] But this strategy can only be applied to those polymers consisting of H and F in neighbor carbon atoms such as PVDF or poly(vinylidene fluoride‐ co ‐hexafluoropropylene) (PVDF‐HFP) [ 24 ] which cannot contribute to ionic transport. Archer's group proposed a more universal method by preparing a kind of soft colloidal glasses HSE that PEO chains were covalently grafted onto silica nanoparticles.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…[ 24–26 ] Nan's group utilized the catalysis of La in dehydrofluorination and prepared poly(vinylidenefluoride) (PVDF)–Li 6.75 La 3 Zr 1.75 Ta 0.25 O 12 (LLZTO) HSE whose ionic conductivity is as high as 5 × 10 −4 S cm −1 at 25 °C. [ 26 ] But this strategy can only be applied to those polymers consisting of H and F in neighbor carbon atoms such as PVDF or poly(vinylidene fluoride‐ co ‐hexafluoropropylene) (PVDF‐HFP) [ 24 ] which cannot contribute to ionic transport. Archer's group proposed a more universal method by preparing a kind of soft colloidal glasses HSE that PEO chains were covalently grafted onto silica nanoparticles.…”
Section: Figurementioning
confidence: 99%
“…The HSE works stable in high‐voltage nickel cobalt manganese oxide (NCM) LMB whose operate voltage is as high as 4.3 V. Therefore, making chemical binding interaction is an effective way to resolve the issue of interphase and facilitate the uniform dispersion of inorganic fillers into polymer matrix thus contributes to flexible HSE with both high conductivity and electrochemical stability. [ 24–26 ]…”
Section: Figurementioning
confidence: 99%
“…By adding Ga/Ta-doped LLZO nanoscale llers, poly(vinylidene uoride) (PVDF)-based electrolytes show superior ionic conductivity and thermal stability, probably due to the interaction between ceramics and dehy-drouorinated PVDF. 31 Compared to homogenous structure, sandwich-type SCE can suppress dendrite as well as form a good interface contact with the electrodes, via regulating the ratio of PEO and Ta-doping LLZO. 32 Furthermore, gelling SCEs by plasticizers, namely forming quasi-solid composite electrolytes (QCEs), together with in situ polymerization, 33,34 has proved to be a feasible way to improve rate and cycle performance of the batteries.…”
Section: Introductionmentioning
confidence: 99%
“…If fast ionic conductors are added into a composite solid electrolyte, the composite can also benefit from the ionic conductivity of the SIEs. Various groups have shown that the electrochemical performance of CPEs can be significantly promoted by including Li + -stuffed ionic-conducting fillers in PEO, [229,[231][232][233][234] PPC, [235] polyacrylonitrile (PAN), [236] PVDF, [237][238][239] and PVDF-HFP [37,240] polymer matrices.…”
Section: Composite Polymer Electrolytesmentioning
confidence: 99%